Association between Mycoplasma pneumoniae infection and adverse pregnancy outcome: a propensity score weighting study - Yang, Caihua; Jiang, Haoxuan; Li, Linyan; Zheng, Ping; Li, Yilei; Wu, Ying (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAfter COVID-19 pandemic, there has been an upward trend in Mycoplasma pneumoniae (M. pneumoniae) infections across Asia. The COVID-19-induced immunological impairment may increase the risk of adverse outcomes in M. pneumoniae-infected patients, yet studies in this area remain limited. We investigated the association between M. pneumoniae infection and adverse pregnancy outcomes in the post-COVID-19 era.MethodsWe conducted a single-center cohort study in Guangzhou, China, from February 2023 to June 2024, involving pregnant women. A total of 186 participants were included, with 49 in the M. pneumoniae group (tested positive for M. pneumoniae immunoglobulin M antibody (MP IgM)) and 137 in the control group. Propensity score weighting analysis was performed to control bias and estimate the effect size.ResultsThe incidence of adverse pregnancy outcomes in the M. pneumoniae group was not significantly different from that in the control group. The odds ratio (OR) for adverse maternal events after propensity score weighting (PSW) was 1.25 (95% confidence interval [CI], 0.62 to 2.55; p = 0.530), and the PSW OR for adverse neonatal events was 0.95 (95% CI, 0.49 to 1.84; p = 0.884). However, in the subgroups of advanced maternal age (AMA, age ≥ 35, n=29) and primiparous women (n=80), the incidence of adverse pregnancy outcomes was significantly higher in the M. pneumoniae group. Additionally, the clinical manifestations of M. pneumoniae infection in the post-COVID-19 era were consistent with those observed prior to the pandemic.ConclusionsIn the post-COVID-19 era, evidence remains insufficient to conclude that M. pneumoniae infection increases the risk of adverse pregnancy outcomes in the general pregnant population. Exploratory subgroup analyses suggest possible signals of risk within subgroups of AMA and primiparous women.